Paraburkholderia tagetis sp. nov., a novel species isolated from roots of Tagetes patula enhances the growth and yield of Solanum lycopersicum L. (tomato) - Chhetri, Geeta; Kim, Inhyup; Kim, Jiyoun; So, Yoonseop; Park, Sunho; Jung, Yonghee; Seo, Taegun (Frontiers in Microbiology, 2023)
A multifunctional, Gram-stain-negative, aerobic, motile by flagella, short-rod shaped bacteria, designated strain RG36T was isolated from roots of marigold plant (Tagetes patula) sampled at Dongguk university, South Korea. A 16S rRNA sequences indicated that the closest phylogenetic neighbors were Paraburkholderia acidiphilla 7Q-K02T (99.0%) and Paraburkholderia sacchari IPT101T (98.9%) of the family Burkholderiaceae. The draft genome size was 8.52 Mb (63.7% GC). The genome contained 7,381 coding sequences. Digital DNA-DNA hybridization (dDDH) and average nucleotide identity (ANI) values of strain RG36T with its most closely related species were only 83.1-88.7% and 27.6-36.7, respectively. Strain RG36T contained Q-8 as the major respiratory quinone and its main fatty acids (>10%) were C16 : 0, C17 : 0 cyclo, C19 : 0 cyclo ω8c and summed feature 8 (comprising C18 : 1 ω7c and/or C18 : 1 ω6c). Strain RG36T accumulates polyhydroxybutyrates (PHB) and exhibits multiple plant growth-promoting properties including production of indole-3-acetic acid (IAA), siderophores, protease, phosphate solubilization and harboring gene clusters for its multifunctional properties. A pot experiment was conducted to evaluate the effect of PGPR on the growth of Solanum lycopersicum L. (Tomato). Result also confirmed the ability of strain RG36T to promote tomato plant growth, especially it increases the yield of tomatoes. Structural assessment of the bioplastic by Fourier transform infrared (FTIR), nuclear magnetic resonance (NMR), and GC-MS spectroscopy, which confirmed the structure of the polymer as PHB. Our study revealed the potential of strain RG36T to promote the growth of tomato plant and fruit yield by stimulating the various phytohormones, which could be use as bio-fertilizers to reduce the use of chemical fertilizers and promotes sustainable agricultural production. The phenotypic, chemotaxonomic and phylogenetic data, and genome analysis showed that strain RG36T represents a novel species of the genus Paraburkholderia, for which the name Paraburkholderia tagetis sp. nov. is proposed. The type strain is RG36T (=KACC 22685T=TBRC 15696T).